Synthesis and Antibacterial Activity of New Oximes, Semicarbazones and Phenyl Hydrazones - M. Hania, Majed (Asian Journal of Chemistry, 2010)
A series of new oximes, semicarbazones and phenyl hydrazones have been synthesized from 2-formylindol, 2-formylfuran and salicylaldehyde and their antibacterial activities have been studied and compared against E. coli which gave different results of activity.